KINERJA ROTARY DRYER PADA PENGERINGAN CHIPS MANIHOT ESCULENTA DALAM PEMBUATAN MOCAF BERDASARKAN VARIASI WAKTU, TEMPERATUR DAN LAJU PENGERINGAN - Yerizam, Yerizam (Politeknik Negeri Sriwijaya, 2019)
Rotary Dryer performance in mocaf making process based on time and drying rate variations aims to produce quality cassava with a moisture content of 12%, therefore the formulation of the problem is focused on the right drying rate so as to produce good quality cassava products with water content in accordance with SNI namely 12%. It can be seen that cassava is a strategic commodity sector in Indonesia, but the cassava drying method still uses sunlight because it has a very low cost because sufficient energy from sunlight is available. This method of drying has several drawbacks, such as contamination of material by impurities from the surrounding environment, highly dependent on the weather, a long drying time, a large area of sun drying and the occurrence of rain that causes the material's water content to become unstable. In the process of drying cassava using a rotary dryer, the drying chamber is first flowed hot air with a temperature of 60Â°C then cassava is inserted at the input, the drying process takes 270 minutes with a cylinder rotation of 3 rpm. During the process several test parameters were measured at each time interval of 60 minutes including measurements of the temperature of the wet ball and the temperature of the dry ball, air rate, sample weight and% water content. The results of these measurements will be used to calculate the drying rate and% water content. From the analysis results obtained a good Drying rate of 2.488070 kg/hour m2 with a water content according to the standard that is 12.5% at 210 minutes